Steps towards an ecology of cognition: A holistic essay - Brauckmann, Sabine (Sign Systems Studies, 2000)
The essay infonns on Gregory Bateson's holistic approach towards an epistemic view of nature. The ecology of mind relies upon a biological holism serving as a methodic tool to explain living "phenomena", like, e.g., communication, learning, and cognition. Starting from the idea, the smallest unit of information, Bateson developed a type hierarchy of learning that is based on a cybernetic view of mind. The communication model focuses on paradoxa caused by false signification. It leads to a pathogenesis of sckizophrenia that is subsumed under the conception of double binds. This ecosystemic perspective of living processes representsa truly (w)holistic theory of nature.